IMPLEMENTASI PENGGUNAAN DANA BEASISWA PEMDA KAYONG UTARA MAHASISWA JURUSAN PIIS FKIP UNTAN PONTIANAK - Karlina, Selfi; Purwaningsih, Endang; Rosyid, Rum (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the implementation of the used of the North Kayong regional government scholarship grants for students of the social sciences education department of Fkip Untan, with descriptive methods. The type of research was qualitative. The data sources in this study were 6 social studies students majoring in social sciences. Data collection techniques in this study were observation, interviews and documentation. The results of this study can be seen that (1) the implementation of the used of the North Kayong regional government scholarship funds by students was partly in accordance with the applicable rules but there were still some that were not in accordance with the rules. (2) discrepancies in the used of scholarship funds by scholarship recipients were indicated by students who still used scholarship funds for their personal needs such as buyed bags, clothes, shoes. The main priority of scholarship funds should be used for college purposes, such as buyed books, photocopyed, printing assignments, and buyed stationery for college. (3) efforts made by the scholarship management to avoid inconsistencies in the used of scholarship funds, namely by monitoring evaluations on each semester and making accountability reports for the used of scholarship funds by students to find out in their used each semester.Keywords: Comdev Students, Local Government Assistance, Scholarship.